Perubahan Reit Pertumbuhan Diameter Batang, sebagai alat perbandingan pertumbuhan diameter diantara - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The objectives of this study were (1) to obtain information on growth rate of different species and (2) to use this information to calculate the rate of change as a tool of comparing growth rate among species. A total of 29 one-hectare permanent growth plots were located in recently logged over forests. Three years after establishment, diameter growth was measured. Based on growth data. coefficient of determination. rate of change of diameter growth and inherent growth rare were calculated. Jr was found that rate ofChange of diameter growth and inherent growth rate were calculated.It was found that rate of changes of diameter growth supplies for a tool of compaaring growth rate among species